Immersive Technologies as a Modern Educational Strategy for Training Future Specialists - Л. Попова (Педагогічна освіта: теорія і практика. Психологія, педагогіка)
Immersive technologies, such as virtual reality (VR), augmented reality (AR), and mixed reality (MR), are revolutionizing modern education by providing interactive, experiential learning environments. This paper examines the impact of these technologies in training specialists across various fields, including healthcare, engineering, pedagogical and vocational education. Immersive tools enhance students’ engagement, practical skills, and critical thinking by simulating real-world scenarios in a safe and controlled environment. Furthermore, they offer personalized learning experiences, promote collaboration, and bridge the gap between theoretical knowledge and practical application. Universities worldwide are increasingly adopting immersive technologies to modernize teaching and enhance learning outcomes. These tools provide dynamic, engaging experiences that enable students to interact with complex material beyond the limits of traditional classroom methods. Interactive learning improves focus and increases knowledge retention. The main principles of building an immersive educational environment are highlighted. With the rapid advancement of digital tools, integrating immersive technologies enhances experiential learning, fosters engagement, and bridges theoretical knowledge with practical skills. The study identifies key tasks, including analysing the pedagogical impact, evaluating the effectiveness of these tools, and identifying challenges. Research findings highlight improved learning outcomes, motivation, and critical thinking among students. The article concludes that immersive technologies are essential for modern education, preparing specialists for dynamic, technology-driven work environments. In the context of rapid technological development, these tools offer new educational possibilities by promoting interactive, experiential learning and bridging the gap between theoretical knowledge and practical application. The purpose of the study is to evaluate the effectiveness of immersive technologies in improving student engagement, retention, and skill acquisition. Key tasks include identifying pedagogical advantages, assessing challenges, and exploring their practical integration. Research findings demonstrate that immersive environments enhance motivation, problem-solving abilities, and critical thinking. The study concludes that immersive technologies represent an essential component of modern educational strategies, equipping future specialists with the competencies needed in evolving, technology-driven industries